2018
DOI: 10.1007/s11886-018-0985-8
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Human Pluripotent Stem Cell-derived Endothelial Cells and Their Therapeutic Utility

Abstract: Purpose of Review Human pluripotent stem cell-derived endothelial cells (hPSC-ECs) emerged as an important source of cells for cardiovascular regeneration. This review summarizes protocols for generating hPSC-ECs and provides an overview of the current state of the research in clinical application of hPSC-derived ECs. Recent Findings Various systems were developed for differentiating hPSCs into the EC lineage. Stepwise two-dimensional systems are now well established, in which various growth factors, small m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
0
15
0
1
Order By: Relevance
“…When Nolan et al engrafted generic, stem cell‐derived ECs into mouse kidneys and livers, they found that the ECs acquired the expression of markers specific to the tissue in which the cells were engrafted. The hPSC‐derived ECs used in this study arise from a mesoderm progenitor but lack tissue and vessel‐type specificity, which may result from developmental immaturity . It would be interesting to determine whether cardiac specificity is induced in these hPSC‐derived ECs cocultured with hPSC‐derived CPCs or CMs and if this specification has an impact on the observed CM maturation.…”
Section: Discussionmentioning
confidence: 99%
“…When Nolan et al engrafted generic, stem cell‐derived ECs into mouse kidneys and livers, they found that the ECs acquired the expression of markers specific to the tissue in which the cells were engrafted. The hPSC‐derived ECs used in this study arise from a mesoderm progenitor but lack tissue and vessel‐type specificity, which may result from developmental immaturity . It would be interesting to determine whether cardiac specificity is induced in these hPSC‐derived ECs cocultured with hPSC‐derived CPCs or CMs and if this specification has an impact on the observed CM maturation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the group of Lee et al have demonstrated that a biocompatible peptide amphiphile (PA) nanomatrix hydrogel substantially improved long-term survival of human pluripotent stem cell (hPSC)-derived ECs in an ischemic hindlimb environment (>10 months). The hPSC-derived ECs, when encapsulated into PA hydrogel, showed better perfusion recovery and higher and more prolonged angiogenic and vascular incorporation capabilities than the bare hPSC-derived ECs [ 29 , 30 ].…”
Section: Bioengineering Approaches For the Treatment Of Padmentioning
confidence: 99%
“…For example, high differentiation efficiency was achieved when CHIR99021 was combined with a lower concentration of VEGF-A and DLL4 (a Notch ligand) in the endothelial cell induction system [66]. DLL4 could enhance endothelial celllineage differentiation and inhibit hematopoietic-lineage differentiation [67]. In addition, CHIR99021 in combination with FGF2, VEGF, and BMP4 could synergistically induce early vascular progenitors (VPs) from hiPSCs with high purities.…”
Section: Endothelial Cells Derived By Bioactive Moleculementioning
confidence: 99%